Grafting starch nanocrystals onto the surface of sisal fibers and consequent improvement of interfacial adhesion in sisal reinforced starch composite. Issue 11 (22nd October 2018) - Chang, Y.; Li, J.J.; Sun, T.S.; Zhou, X.D.
ABSTRACT: Starch nanocrystals (SNCs) were obtained by the hydrolysis of waxy starch and used to improve the interfacial adhesion of a composite of sisal fibers and starch. Sisal fibers were first treated with acrylic acid (AA), and the modified fibers were then reacted with SNCs to form ester groups. The grafted fibers were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The FTIR and XPS results showed that the SNCs were successfully grafted onto the surface of SF‐AA, and an ester linkage was formed during the reaction of AA with the SNCs. The SEM analysis showed that the SNCs were distributed over the fiber surface. Tensile tests and pull‐out tests were also performed utilizing a two‐parameter Weibull distribution analysis to study the effect of the grafted SNCs on the mechanical and interfacial properties. Compared to the untreated fibers, the interfacial shear strength of the grafted SNCs fibers increased by 79.3%. Therefore, the structural similarity between starch and the SNCs contributed towards their compatibility and improved interfacial properties, with the introduction of SNCs being used as an alternative material for fiber surface modification. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47202. Abstract :